World grain trade statistics: exports by source and destination 1968/69 - Food and Agriculture Organization of the United Nations; United nations ([Rome]: Food and Agriculture Organization of the United Nations, 1968)
The material presents data for 1968/69 world grain statistics and export by source and destination.
Serial.
rpm 31/01/2019
Loans
Keywords: Grain trade